1974
DOI: 10.1159/000152672
|View full text |Cite
|
Sign up to set email alerts
|

Sampling Variances in Twin and Sibling Studies of Man

Abstract: The sampling variances in twin and sibling studies of man for estimation of intraclass correlation coefficients and their relation to heritabilities are evaluated. For twins and full-sibs the higher the estimated heritability of a trait the smaller the sampling variance. With increase in the number of twin sets or of full-sibships studied, the sampling variances decrease by their proportions. Twin and full-sib studies with lower heritabilities (h2 < 0.25) need at least 50 sibships to obtain a signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1976
1976
2003
2003

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 1 publication
(1 reference statement)
0
3
0
Order By: Relevance
“…Such data are basic to genetic studies of caries and periodontal status and should be obtained along with phenotype and risk-factor data, and their effects should be treated as covariates. Kang et al (1974) investigated the efficiency of the twin half-sib design relative to sample size. These workers concluded that the variance of estimates of the genetic half-sib intra-class correlation coefficient stabilized with 100 half-sibships.…”
Section: Discussionmentioning
confidence: 99%
“…Such data are basic to genetic studies of caries and periodontal status and should be obtained along with phenotype and risk-factor data, and their effects should be treated as covariates. Kang et al (1974) investigated the efficiency of the twin half-sib design relative to sample size. These workers concluded that the variance of estimates of the genetic half-sib intra-class correlation coefficient stabilized with 100 half-sibships.…”
Section: Discussionmentioning
confidence: 99%
“…They are also likely to be more similar in age than half-siblings in families formed following the death of a spouse or divorce. Despite its advantages, including efficiency in relation to sample size, 24 Potter's 23 encouragement to researchers to use the half-sib model to study common dental diseases has so far gone unheeded. However, Harrap and colleagues have used the model productively in a study of cardiovascular risk factors in Australians.…”
Section: The Twin Half-sib Modelmentioning
confidence: 99%
“…A model for the analysis of data from MZ twin " half-sibships " is developed here and its usefulness is explored. For previous descriptions and applications of the model see Bader et al (1973), Bingle (1974) Kang et al (1974), Nance et al (1974), and Nance (1975).…”
Section: Introductionmentioning
confidence: 99%